CSA Indicators Database Summary and Key Findings - Quinney, Marie; Bonilla Findji, Osana; Jarvis, Andy (2016)
Companion Document for CSA Programming and Indicator Tool: 3 Steps for increasing programming effectiveness and outcome tracking of CSA interventions. In the context of a collaboration with USAID Feed the Future, the CSA programming and indicator Tool has been designed to contribute to address both, the need of good instruments for programming and better metrics for tracking outcomes and impact and to allow multiple development agencies and agricultural focused programs to share a common framework on how they are currently addressing Climate-Smart Agriculture and how they can make their future programming process more climate-smart. The CSA Programming and Indicator Tool helps to examine the scope of a given program or intervention through the three dimensional lenses of Climate Smart Agriculture (Productivity/Income, Adaptation and Mitigation). This tool strengthens the planning phase of interventions in order to ensure that all potential CSA related outcomes (beyond productivity/income pillar) are properly included in the M&E design.